Individual-level loss aversion in riskless and risky choices - Simon Gächter; Eric J. Johnson; Andreas Herrmann (Institute for the Study of Labor (IZA), 2007)
Loss aversion can occur in riskless and risky choices. Yet, there is no evidence whether people who are loss averse in riskless choices are also loss averse in risky choices. We measure individual-level loss aversion in riskless choices in an endowment effect experiment by eliciting both WTA and WTP from each of our 360 subjects (randomly selected customers of a car manufacturer). All subjects also participate in a simple lottery choice task which arguably measures loss aversion in risky choices. We find substantial heterogeneity in both measures of loss aversion. Loss aversion in the riskless choice task and loss aversion in the risky choice task are highly significantly and strongly positively correlated. We find that in both choice tasks loss aversion increases in age, income, and wealth, and decreases in education.
Keywords: 330; Verlust; Risikoaversion; Entscheidung; Test; Willingness to pay; Deutschland